To create, to separate or to construct: an alternative for a recent proposal as to the interpretation of brʼ in Gen 1:12:4a - Becking, Bob (The journal of Hebrew scriptures, 2010)
Recently, Ellen van Wolde has proposed that the Hebrew verb ברא in Genesis 1 should be understood as ‘(to) separate.’ She also suggests that this is a new proposal. In this article, we maintain: (1) The idea has roots in nineteenth century scholarship; (2) the proposal is week from an etymological perspective; (3) an understanding of ברא as ‘(to) separate’ does not take into account that ברא is not used with prepositions; (4) as far as we can see— and contrary to Van Wolde’s statement— an active participle of the verb ברא meaning ‘creator’ does occur in Biblical Hebrew; (5) the ‘sea-monsters’ are not separated from the other marine animals; (6) a survey of parallelisms and word-pairs yields that the verb ברא was part of a semantic field characterized by ‘building; constructing; making;’ (7) there is no phrase or sentence in the HB in which ברא must be translated as ‘(to) separate’. Finally we offer the alternative to render ברא with ‘(to) construct’ as means to indicate that Genesis 1 praised the divine construction of cosmos and life, while at the same time avoided an anthropomorphism that the use of the verb בנה might have raised.